2002
DOI: 10.1121/1.4778303
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sweep cycle for time-varying comb filters for binaural dichotic presentation to improve speech perception in sensorineural hearing impairment

Abstract: In a previous investigation [P. C. Pandey et al., J. Acoust. Soc. Am. 110, 2705 (2001)], a scheme using binaural dichotic presentation was devised for simultaneously reducing the effect of increased temporal and spectral masking in bilateral sensorineural hearing impairment. Speech was processed by a pair of time-varying comb filters with passbands corresponding to cyclically swept auditory critical bands, with the objective that spectral components in neighboring critical bands do not mask each other and swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The scheme was implemented using a pair of time varying comb filters with pre-calculated set of coefficients, which were selected in steps such that a cyclic sweeping of the pass bands occur. An experimental evaluation conducted on normal subjects with simulated hearing loss with constant sweep cycle of 20 ms provided improvement in the recognition scores and perception of place and duration features [6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The scheme was implemented using a pair of time varying comb filters with pre-calculated set of coefficients, which were selected in steps such that a cyclic sweeping of the pass bands occur. An experimental evaluation conducted on normal subjects with simulated hearing loss with constant sweep cycle of 20 ms provided improvement in the recognition scores and perception of place and duration features [6].…”
Section: Introductionmentioning
confidence: 98%
“…Masking takes place primarily at the peripheral auditory level, while integration of information takes place at higher levels in the auditory system. Earlier investigations have shown that processing schemes with binaural dichotic presentation reduced the effect of increased masking for persons with residual bilateral hearing [3]- [6].…”
Section: Introductionmentioning
confidence: 99%